Analysis of Patient Satisfaction with Dental Health Services at the Community Health Centre - Fitri Sulviana; Ali Harokan; Lilis Suryani; Akhmad Dwi Priyatno (Lentera Perawat, 2024)
Oral and dental health services to improve oral and dental health, prevent and cure diseases and restore oral and dental health for individuals, families, groups or communities in a complete, integrated and quality manner. Limited facilities and infrastructure, lack of health workers and lack of medical equipment in the dental room, so that the services provided are not in line with community expectations. This study aims to determine the factors associated with patient satisfaction with dental health services. This research design is quantitative with a crosssectional approach.  The population of this study were people who visited the Puskesmas dental clinic. The sample in this study amounted to 87 people. The sampling method uses purposive sampling. This research was conducted on 08 February - 8 March 2024. Data collection using questionnaires. Bivariate data analysis using Chi-Square test and multivariate logistic regression. The results showed that there was a relationship between responsiveness (p value 0.003), assurance (p value 0.011), and empathy (p value 0.05) to dental health service satisfaction. The most dominant factor with dental health service satisfaction is Responsiveness (p value 0.002) (OR 5.50). For the Puskesmas to provide fast and responsive service in providing health services.